Tinjauan Yuridis Pembagian Harta Perkawinan Menurut Hukum Islam Dan Hukum Perdata : Studi Kasus Putusan Nomor; 0752/Pdt.G/2015/PA.JB - Novitaningsih Dwi Trisnawati; M. Yazid Fathoni (Private Law, 2022)
This study aimed to find out the marriage wealth distribution based on Islamic law and Civil law in verdict number 0752/Pdt.G/2015/PA.JB. The research used a normative research method with the law, conceptual, and case approaches. The research results of the judge's decision decided that the plaintiff's lawsuit was partially granted by stating that the plot of land and the building that became the object of the lawsuit was the defendant's innate property while the cost of renovating the house was the plaintiff's innate property. The object of dispute in this lawsuit was not Joint Property (Gono-Gini) because of Article 35 of Law Number 1 of 1974 jo, Article 1 letter (f) Compilation of Islamic Law, which meant the joint property was wealth obtained from husband and wife during their marriage bond. The distribution of marital wealth could be determined otherwise if both parties had a marriage agreement, either before or after the marriage took place. The marriage agreement was made in writing and ratified by the marriage registrar or notary. This marriage agreement applied as law for those who created it and also applied to third parties as long as they were involved.